Databases in Networked Information Systems 6th International Workshop, DNIS 2010, Aizu-Wakamatsu, Japan, March 29-31, 2010. Proceedings - Kikuchi, Shinji; Sachdeva, Shelly; Bhalla, Subhash; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2010)
This book constitutes the refereed proceedings of the 6th International Workshop on Databases in Networked Information Systems, DNIS 2010, held in Aizu-Wakamatsu, Japan in October 2010. The 13 revised full papers presented together with 9 invited talks and 1 keynote lecture were carefully reviewed and selected for inclusion in the book. The workshop generally puts the main focus on data semantics and infrastructure for information management and interchange. The papers are organized in topical sections on networked information systems: infrastructure, access to information resources, information and knowledge management systems, information extraction from data resources, and geo-spatial decision making.
Networked Information Systems: Infrastructure -- Data Management Challenges in Cloud Computing Infrastructures -- Managing Dynamic Mixed Workloads for Operational Business Intelligence -- A Study on Workload Imbalance Issues in Data Intensive Distributed Computing -- Information Extraction, Real-Time Processing and DW2.0 in Operational Business Intelligence -- On Realizing Quick Compensation Transactions in Cloud Computing -- Optimization of Query Processing with Cache Conscious Buffering Operator -- Access to Information Resources -- Usability Confinement of Server Reactions: Maintaining Inference-Proof Client Views by Controlled Interaction Execution -- AccKW: An Efficient Access Control Scheme for Keyword-Based Search over RDBMS -- Information and Knowledge Management Systems -- Social Intelligence Design for Knowledge Circulation -- Agent-Based Active Information Resource and Its Applications -- Semantic Interoperability in Healthcare Information for EHR Databases -- Adaptive Integration of Distributed Semantic Web Data -- Managing Groups and Group Annotations in madcow -- Semantic Network Closure Structures in Dual Translation of Stochastic Languages -- Information Extraction from Data Resources -- VisTree: Generic Decision Tree Inducer and Visualizer -- Semantics Extraction from Social Computing: A Framework of Reputation Analysis on Buzz Marketing Sites -- An Approach to Extract Special Skills to Improve the Performance of Resume Selection -- EcoBroker: An Economic Incentive-Based Brokerage Model for Efficiently Handling Multiple-Item Queries to Improve Data Availability via Replication in Mobile-P2P Networks -- Interface Tailoring by Exploiting Temporality of Attributes for Small Screens -- Geo-spatial Decision Making -- Towards K-Nearest Neighbor Search in Time-Dependent Spatial Network Databases -- Spatial Query Processing Based on Uncertain Location Information -- Skyline Sets Query and Its Extension to Spatio-temporal Databases -- Implementation of Geographic Search Methods for Lunar Objects.
Keywords: Computer science; Computer Communication Networks; Database management; Data mining; Information systems; Multimedia systems; Computer Science; Database Management; Data Mining and Knowledge Discovery; Information Systems Applications (incl.Internet).; Multimedia Information Systems; User Interfaces and Human Computer Interaction; Computer Communication Networks